Analysis of Pressure Changes in the Sihi Pump Output Pipe at PT. Mashud Bersaudara Internasional - Lutfi, Mohammad; Afifah, Rohima Sera; Mukmin, M. Nur; Rahman, Khairul (Jurnal Pendidikan Tambusai, 2024)
Pipeline redesign was conducted at the LPG filling and distribution station of PT. Mashud Bersaudara Internasional to address excess pressure in the piping system during the LPG filling process on the filling skid. This research aims to analyze the pressure changes in the Sihi pump output pipe subsequent to the installation of a larger Sihi pump on the LPG filling skid line. Pressure changes in the pipe were analyzed using the continuity and Bernoulli equations. The research results indicated that the pressure increase, which triggered the activation of the pressure safety valve in the return pipeline, was due to the replacement of the Sihi pump with a larger capacity model. Prior to changing the size of the return pipe, the pressure was 8.535 Bar. After the replacement, the pressure in the Sihi pump output pipe dropped to 7.5525 Bar, which is below the pressure threshold of the pressure safety valve. Thus, the pipeline redesign successfully resolved the excess pressure issue.